Skin tissue exposure of once- versus twice-daily topical ozenoxacin 2% cream: a Phase I study in healthy volunteers. (September 2014) - Gropper, Savion; Albareda, Nuria; Santos, Benjamin; Febbraro, Salvatore
ABSTRACT: : In this Phase I study, healthy volunteers (n = 24) were randomly allocated to receive either one or two 0.2-g applications per day (12 h apart) of ozenoxacin 2% cream on three different areas of the back for 3 consecutive days. Ozenoxacin concentrations were measured in tape stripping samples (from the stratum corneum) and in skin punch biopsy samples (from the epidermis and dermis) taken predose from selected dosing areas on study days 2, 3 and 4. Ozenoxacin concentrations were high in the stratum corneum and were approximately twofold greater for the twice- versus once-daily application. Ozenoxacin concentrations were low in the epidermis and were higher for the twice- versus once-daily application. Ozenoxacin concentrations in the dermis were below the limit of quantitation on most study days.